Influence Self-Efficacy, Emotional Intelligence, and Learning Independence on Critical Thinking Skills of Class X Accounting Students at State Vocational High Schools in South Jakarta - Nandita Dwi Pratiwi; Susi Indriani, S.E., M.SAk., Ph.D; Sri Widi Lestari, S.Pd., M.Pd. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to test and analyze the influence of self-efficacy, emotional intelligence, and learning independence on the critical thinking skills of tenth-grade Accounting students. This research employed a quantitative approach using primary data collected through questionnaires. The population of this study consisted of 250 students, with a sample of 154 respondents selected using probability sampling with a simple random sampling technique. The data were analyzed using SPSS v26 through descriptive statistical analysis, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The findings revealed that (1) self-efficacy have a significant influence on student’s critical thinking, (2) emotional intelligence does not have significant influence on student’s critical thinking, (3) learning independence have a significant influence on student’s critical thinking, (4) self-efficacy, emotional intelligence, and learning independence have a significant influence on student’s critical thinking.